Logistics Strategies Assessment for Small Coffee Producers in Chiapas, Mexico - Yair Romero-Romero; Loecelia Ruvalcaba Sánchez; Julia Sánchez-Gómez (International Journal of Supply Chain Management, 2021)
Coffee production represents the livelihood of many peasant families in underdeveloped countries. In Mexico, coffee production has social, ecological, and economic significance. However, the Mexican industry coffee needs to determine a logistic strategy for improving its competitiveness. This work proposes a methodology to help coffee producers in Chiapas, Mexico. This methodology has four stages. First, we did SWOT Analysis to understand the environment of the coffee sector from a literature review. Second, from SWOT analysis, a survey was designed. An expert group in coffee production linked to Chiapas coffee producers answered this survey. We use Cronbach's alpha coefficient to validate answers. Third, we assessed external and internal factors matrices to define generic strategies. Finally, it selected the best option from the Quantitative Matrix of Logistics Strategies. The results show several areas of opportunity for coffee producers concerning strengths and opportunities. The resulting logistic strategy is oriented to increase the participation of coffee products in the current market —this action help to make a differentiation of the brand through the denomination of origin and geographical indication.